2022
DOI: 10.1101/2022.08.15.503980
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phenotype integration improves power and preserves specificity in biobank-based genetic studies of MDD

Abstract: Biobanks often contain several phenotypes relevant to a given disorder, and researchers face complex tradeoffs between shallow phenotypes (high sample size, low specificity and sensitivity) and deep phenotypes (low sample size, high specificity and sensitivity). Here, we study an extreme case: Major Depressive Disorder (MDD) in UK Biobank. Previous studies found that shallow and deep MDD phenotypes have qualitatively distinct genetic architectures, but it remains unclear which are optimal for scientific study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 93 publications
(181 reference statements)
1
14
0
Order By: Relevance
“…We then imputed Lifetime MDD in the entire cohort, using 216 other phenotypes in the biobank, chosen regardless of their putative relationship with MDD, using Soft-Impute [134] (a variant of principal component analysis that accommodates missing data, and uses observed phenotype data to identify latent factors). We were able to show that the top phenome-wide factors capture pleiotropic axes for MDD, allowing us to identify genetic effects that are specific to lifetime MDD (which stood in for the gold standard MDD cases) [126]. Remarkably, we found that the one-item self-assessment measures (which capture general dysphoria), residualized of these latent factors, index core, MDD-specific biology.…”
Section: Trait1mentioning
confidence: 75%
See 2 more Smart Citations
“…We then imputed Lifetime MDD in the entire cohort, using 216 other phenotypes in the biobank, chosen regardless of their putative relationship with MDD, using Soft-Impute [134] (a variant of principal component analysis that accommodates missing data, and uses observed phenotype data to identify latent factors). We were able to show that the top phenome-wide factors capture pleiotropic axes for MDD, allowing us to identify genetic effects that are specific to lifetime MDD (which stood in for the gold standard MDD cases) [126]. Remarkably, we found that the one-item self-assessment measures (which capture general dysphoria), residualized of these latent factors, index core, MDD-specific biology.…”
Section: Trait1mentioning
confidence: 75%
“…We need a set of well phenotyped cases to seed imputation, but how to maximize imputation's effectiveness remains an open question, so it's not possible to provide robust estimates of the number of interview-based cases required. As an example of what is possible, imputation using data from a questionnaire-based measure of MDD from 67,164 UK biobank into 337,126 individuals with a single-item measure increased both the number of risk loci identified and out-of-sample prediction of MDD accuracy, while preserving better specificity to MDD than the single-item measure [126].…”
Section: Trait1mentioning
confidence: 99%
See 1 more Smart Citation
“…As MR results show that PHQ9 symptoms are more likely endorsed due to non-MDD phenotypes that index general dysphoria than MDD, we further ask if this means that genetic studies on PHQ9 symptoms are less likely to lead us to identify MDD-specific biology. To do this we computed 10-fold cross-validated PRS on all PHQ9 and WorstEpisode symptoms in UKBiobank, and used these to predict MDD and non-MDD phenotypes explored above, obtaining the ratio between their prediction R 2 (PRS Pleiotropy = R 2 non-MDD /R 2 MDD ) 33 . A higher PRS Pleiotropy means lower specificity of a PRS for MDD.…”
Section: Resultsmentioning
confidence: 99%
“…For all quantitative phenotypes, including neuroticism, we evaluated accuracy using ordinary R 2 . PRS Pleiotropy 33 is calculated for each PHQ9 and WorstEpisode symptom using the ratio of its PRS predictions on 50 non-MDD phenotypes and its prediction on LifetimeMDD in UKBiobank or ICD10-based MDD in iPSYCH cohorts (PRSPleiotropy = R 2 non-MDD / R 2 MDD , Supplementary Tables 10-12 ).…”
Section: Methodsmentioning
confidence: 99%